Comparative analysis of coach motives in a commercial and non-profit sports organization - Ilyina N.L. ,; Lutkova N.V. ,; Egorenko L.A. ,; Baranova M.V. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to compare the degree of expression of motives for professional activity among coaches of a commercial and non-profit sports organization. Methods and structure of the study. The technique “Possibility of realizing motives” (PRM) by V.I. Dominyaka, E.A. Rodionova. Team sports coaches from the city of St. Petersburg (n=40, men, age 24–28 years, professional experience from 3 to 5 years) took part in the study. "Footboland" is a children's football school (commercial organization) and a sports school in the Krasnoselsky district of St. Petersburg (non-profit organization). Results and conclusions. Evidence was obtained that in a non-profit organization, the following motives are important for trainers: respect from other people, social prestige, career growth, the excitement of professional competition. Trainers of a non-profit organization believe that the organization does not provide them with the opportunity to fully realize these motives. In a commercial organization, the most important motives for trainers are: increasing their professional competence and satisfaction from the process of activity. A commercial organization helps trainers realize such motives for professional activity as satisfaction from the process of activity, a sense of freedom and independence in decision-making, and opportunities for self-realization in the profession. It is advisable to use the obtained data in working with coaching staff, both at the time of accepting a specialist into an organization in order to clarify the organization’s real capabilities in satisfying the coach’s motivational orientations, and in the process of his professional implementation to prevent professional burnout.